Radiological Approach to Liver Infections - Kumar, Abhinandan; Garg, Dollphy; Gupta, Pankaj (Journal of Gastrointestinal and Abdominal Radiology, 2023)
Liver infections are a common and appropriate management depends on the accurate diagnosis. Imaging is an important part of the workup of patients with suspected liver infections. The imaging appearances depend on the causative agent. When imaging features are seen in context of the clinical presentation, biochemical features, and predisposing condition, a specific diagnosis is possible in a significant proportion of patients. In this review, we discuss the imaging-based approach to liver infections.
Keywords: liver; infection; imaging